Predictors of psychological well-being of adolescents' parents - Keresteš, Gordana (Array, 2012)
Informed by theories about processes in families with adolescent children, this study examined the contribution of self-perceived decline in physical and cognitive functioning related to midlife, marital satisfaction, and parent-child conflict to psychological well-being of parents of young adolescents. Parental well-being was conceptualized within Ryff's multidimensional model, which encompasses six dimensions: Autonomy, Self-Acceptance, Environmental Mastery, Positive Relationships with Others, Personal Growth, and Purpose in Life. In examining relationships between parental well-being and supposed predictors, sociodemographic variables (parental age and education), perceived general life stress, and perceived available social support were controlled for. Participants were Croatian mothers (N = 356) and fathers (N = 328) whose oldest child was transitioning to adolescence. Overall, the patterns of associations between the studied predictors and well-being dimensions were similar for mothers and fathers. The main finding of the study was that individual differences in the psychological well-being of adolescents' parents may be more attributable to self-perceived midlife changes (particularly for mothers) and marital satisfaction (particularly for fathers) than to perceived level of parent-adolescent conflict.